Statistical Characterisation of the Delay and Performance Analysis in 3D Relay Networks - Hashemi, Hadi; Olyaee, Maryam; Soret, Beatriz; Aguayo-Torres, María del Carmen; Buzzi, Stefano (IEEE, 2024)
This article investigates a multi-tier 3D network that models a hybrid space-air-ground communication system and two main relay scenarios. In the first scenario, the aerial tier, consisting of entities such as Unmanned Aerial Vehicles (UAVs) or aircrafts, uses the space layer, represented by satellites, to connect to ground User Equipment (UE) devices or ground stations. In the second scenario, the space layer cooperates with satellites in a lower orbit or with aerial devices to communicate with ground-based devices. In both scenarios, it is assumed that the device acting as a relay is distributed throughout its tier according to a Poisson Point Process (PPP), and randomly selected from the coverage area that depends on the position of the source and destination devices. For both scenarios, the paper calculates the distribution function for the link distance, which permits to obtain the average delay of signal propagation. Further, in the paper the outage capacity and ergodic rate expressions for the amplify and forward (AF) and decode and forward (DF) relaying strategies under the shadowed-Rician fading channel model are derived. Also, the asymptotic behavior in the high-SNR regime is analyzed. These novel analytical expressions provide insights of the fundamental performance limits of integrated terrestrial and non-terrestrial wireless networks.
Keywords: Comunicaciones digitales; Relays; Space vehicles; Satellites; Orbits; Analytical models; Low earth orbit satellites; Geometry; Three-dimensional displays; Stochastic processes; Satellite broadcasting; Multi-tier network; Aerial layer; Space layer; Amplify and forward (AF) relay; Decode and forward (DF) relay; Distance distribution; Stochastic geometry; Propagation delay